SYNONYMIC ASYNDETIC SUBORDINATE UTTERANCES OF POLYPREDICATIVE STRUCTURES WITH THE PARTICIPIAL AND GERUNDIAL HEAD LEXEMES (on the material of French fiction of the 20th – the beginning of the 21st centuries) - Anastasiia V. Lepetiukha (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In the article absolute pre-, inter- and postpositive grammaticalized and typical agrammaticalized (conventional in discourse but non-conventional in language) participial and gerundial turns and postpositive object participial turns are distinguished and analyzed. They are defined as synonymic subordinate utterances with implicit-explicit predication with the participial and gerundial head lexemes. The goal of this article is to highlight the semantic-syntactic types of synonymic absolute participial and gerundial turns and of object participial turns and to justify their co(n)textual (linguistic and situational) pertinence. Achieving the goal involves solving such problems as: to establish the structural typologies of the participial and gerundial synonymic discourse innovations; to identify the semantic meanings of the primary and actualized structures; to determine the degree of the co(n)textual pertinence of all the members of the synonymic chain within the functional-semantic macrofield. In this research the method of the inverse (discourse → language) reconstruction of virtual (linguistic) transformational processes and the «alternative» linguistic experiment are used to justify the co(n)textual pertinence of the actualized synonymic structure. The analyzed constructions are defined as one- and two-basis synonymic transforms of the primary subordinate proposition actualized in the form of compressed discourse innovations-preferential options with temporal, causal, hypothetical and explicative semantic meanings. The such structural types of these constructions are distinguished: a) absolute participial and gerundial turns build on the models: S (subject) + P pr / p (participle present / past), P pr / р or (D) (stimulator of identification of referent) S + G pr / p (gerund present / past), G pr / p, G p + S; b) оbject participial turns build on the model P pr / р + C (object). By means of the inverse reconstruction all the members of virtual synonymic chains are identified and the degree of their co(n)textual pertinence is experimentally determined. It is revealed that the author uses the strategies of the simplification or the complication of the information to the recipient according to some pragmatic planning of the narration, his communicative intention or his idiostylistic peculiarities. It is proved that the «alternative» linguistic experiment can fail in the case of the implication of some referents non-exteriorized in either pretext or posttext